BULLYING AND ITS IMPACTS TOWARD AUGUST IN R.J. PALACIOS WONDER - RIFKY MUSANTO (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
ABSTRACT Musanto, Rifky. 2019. Bullying and Its Impacts toward August in R.J. Palacio’s Wonder. English Department. State University of Surabaya. Advisor: Pratiwi Retnaningdyah, Ph.D. Keywords: verbal, behavioral, symbolical bullying, and impacts Palacio’s Wonder tells a story of a boy with facial deformation. His facial deformation makes his face look different than the other. Some of his friends, especially Julian, call him bad such as monster, zombie, and so on. It explains that the real situation to discuss is about the bully and how it gives impacts. Therefore, if it has to be formulated into questions, it can be listed to two points as follows: (1) how is bullying toward August depicted in R. J. Palacio’s Wonder? And (2) What are the impacts of the bullying toward August in R. J. Palacio’s Wonder? To reveal those questions, this research uses Olweus’s perspective on bully (1993) with additional points of the types from conceptions of Barry E. McNamara and Francine J. McNamara (1997). The approach of this research is textual approach, the technique of data collection is documentation, and the technique of data analysis is interpretation. This research results that August receives some kinds of bullying such as verbal, behavioral, and symbolical. Those affect to August’s life such as traumatic disorder (anxiety) and lack of social motivation. However, August finally can fight back against bullying by making achievement in his school.